Multifunctional MnO2-based nanozyme scaffold with microenvironment-responsive release for immunomodulation and neuroregeneration in spinal cord injury applications - Ling Peng; Yusong Pan; Jun Tao; Cuilian Wei; Qianqian Liu; Run Huang; Xiuling Lin; Rui Yue (Chemical Engineering Journal, 2026)

Soil deposition reduces bacterial network complexity and stability by shifts in life-history strategies on the Loess Plateau of China - Yanqing Guo; Hailun Zhang; Shunxiang Yao; Bin Zhu; Rui Ma; Xiuling Li; Qianjin Liu; Qiqi Sun; Shengli Guo; Yaxian Hu; Lanlan Du (Applied Soil Ecology, 2026)

Corrigendum to “PMs-Ti4+-based plasma extracellular vesicles glycoproteomics and its application in lung cancer” [Anal. Chim. Acta 1405 (2026) 345449] - Xinxin Zheng; Fangfang Xiong; Yanyan Zhao; Xiuling Li; Zhiyu Liu; Xinmiao Liang (Analytica Chimica Acta, 2026)

Autophagy in Aquatic Animals: A Double‐Edged Sword in Environmental Stress Response and Nutritional Mitigation Strategies - Hui Gao; Yue Liu; Xiuling Li; Wenxia Wang (Reviews in Aquaculture, 2026)
The intensification of aquaculture and global climate change expose aquatic animals to multifaceted environmental stressors, triggering diverse stress‐response cascades to mitigate cellular damage and preserve physiological homeostasis. Autophagy, an evolutionarily conserved lysosome‐dependent catabolic process that degrades damaged or redundant cellular components to maintain cellular homeostasis and physiological functions, plays a crucial role in the environmental stress response in aquatic animals. This review systematically summarizes the modulatory influence of major environmental stressors (physical, chemical, and biological) on autophagic activity in aquatic species. Overall, the regulatory network mainly centers on oxidative stress responses, mitochondrial quality control, the 5′‐adenosine monophosphate‐activated protein kinase (AMPK)/mechanistic target of rapamycin kinase complex 1 (mTORC1) signaling axis, mitogen‐activated protein kinase (MAPK) cascade, endoplasmic reticulum (ER) stress and related pathways. The dynamic equilibrium of autophagic flux dictates the cellular fate balance between adaptive survival and stress‐induced injury: physiologically moderate autophagy functions as a cytoprotective and adaptive mechanism that confers stress resilience, whereas dysregulated autophagy (either impaired flux or excessive activation) disrupts cellular homeostasis and shifts cell fate toward apoptotic death. Additionally, this review explores the potential of nutritional intervention strategies to modulate autophagic activity and alleviate stress‐induced damage in aquatic animals. Finally, key challenges and prospective research directions are proposed, providing a theoretical framework for deciphering stress resistance mechanisms in aquatic animals and advancing sustainable aquaculture practices.

Network Reconfiguration Underlies Compensatory Muscle Control Across Force Gradients: Parallel Functional Network Evidence from EEG and sEMG - Xiaoguang Liu; Pengyuan Lin; Yutong Wang; Tie Liang; Xiaodong Wang; Jun Li; Peng Xiong; Xiuling Liu (Annals of Biomedical Engineering, 2026)

Computational modeling of prefrontal-amygdala circuits links functional connectivity alterations to circuit-level mechanisms in major depression - Licong Li; Fukuan Zhang; Shuaiyang Zhang; Jinzhao Wei; Kun Wang; Bote Zheng; Jianli Yang; Xiuling Liu (Journal of Computational Neuroscience, 2026)

Identification of the SlRCC1 gene family and characterization of SlRCC1-13 in cold stress response in tomato (Solanum lycopersicum) - Huixin Zhang; Xueyao Zeng; Yixiao Bai; Yuxin Liu; Rui LV; Fulei Mo; Mingfang Feng; Shusen Liu; Xiuling Chen; Aoxue Wang (Plant Science, 2026)

PMs-Ti4+-based plasma extracellular vesicles glycoproteomics and its application in lung cancer - Xinxin Zheng; Fangfang Xiong; Yanyan Zhao; Xiuling Li; Zhiyu Liu; Xinmiao Liang (Analytica Chimica Acta, 2026)

Steering Ce atoms as an electronic reservoir in Tpy-regulated Bi2Te3 nanosheets for enhanced CO2 reduction to formate - Yupeng Li; Xinrui Liu; Shu Liu; Dairong Chen; Xiuling Jiao; Yuguo Xia (Chemical Engineering Journal, 2026)

Carbon input manipulation significantly alters soil CO2 and CH4 fluxes across stand ages in boreal birch forests of China - Minglei Gao; Xiuling Man; Tijiu Cai; Shuo Zhang; Qiaojuan Liu; Hanxiong Song; Changhui Peng (Agricultural and Forest Meteorology, 2026)

Moisture migration, ice lenses and frost heave characteristics of soils under one-dimensional freezing action: A critical literature review - Xiuling Ren; Fujun Niu; Degou Cai; Jing Luo; Qihao Yu; Minghao Liu; Guoan Yin; Zeyong Gao (Earth-Science Reviews, 2026)

Coordination chemistry-guided construction of hierarchical lignin-derived porous carbon with dual Lewis acid–base sites for synergistic CO2 capture - Xinxin Niu; Li Bai; Xiuling Xu; Fujun Wang; Shuai Zhu; Yixian Xue; Zhi Liu; Zhao Chen (Chemical Engineering Journal, 2026)

Metagenomics and targeted metabolomics uncover concomitant gut microbiota dysbiosis and bile acid metabolism alteration in norfloxacin-exposed Bufo gargarizans tadpoles - Yanjiao Song; Xiuling Song; Xiaoli Liu; Ling Jiang; Lihong Chai (Aquatic Toxicology, 2026)

Variations and driving factors of soil respiration components over stand age in boreal birch forests in China - Minglei Gao; Xiuling Man; Qiaojuan Liu; Tijiu Cai; Changhui Peng (Plant and Soil, 2026)

Integrating computational and biological approaches for the discovery of putative MmpL3 inhibitors against Mycobacterium tuberculosis - Likun Zhao; Hongfu Li; Xiuling Ma; Jiahao Sun; Henry H.Y. Tong; Huitao Huang; Hongtou Chan; Xiaojun Yao; Huanxiang Liu; Qianqian Zhang (Molecular Diversity, 2026)

Acidic-heating induced protein fibrils derived from perilla seed residues: spotlight on assembly behavior, conformational changes and structure-function relationships - Xiquan Li; Jun Yang; Liting Feng; Hao Guo; Xiaochen Liu; Xiuling Zhang; Wentao Zhang (Food Hydrocolloids, 2026)

YIP: optimized YOLOv11-seg for accurate intramuscular fat percentage prediction in pigs using non-invasive ultrasound imaging - Junhao Zhang; Hang Jiao; Genyuan Li; Hanhan Li; Chenglin Li; Pengsheng Dong; Yan Liu; Bo Jiang; Peng Shang; Feng Yang; Chunli Li; Xinjian Li; et al. (Science China Life Sciences, 2026)

Span80 induced orderly diffusion of monomer for the construction of small pore volume polyamide nanofiltration membrane with high Li/Mg separation ratio - Lu Gao; Yue Miao; Xiaowen Huo; Yingying Zhao; Zhaojing Jing; Xiuling Liu; Haitao Wang; Ning Fan; Qiuying Jia; Kai Ren; Jun Li; Na Chang (Desalination, 2026)

Silica Nanoparticles Induce BV-2 Cells Autophagy Via activation of NLRP3 inflammasome and CaMKK2 Signaling Pathways - Tianxiang Liu; Mingqian Wang; Yuanyuan Zhang; Li Yang; Jia Zhang; Hongzhu Wei; Xinyue Li; Huan Pang; Jiali Li; Zhixuan Luo; Mengyue Liu; Haiying Du; et al. (Molecular Neurobiology, 2026)

Characterization and source apportionment of heavy metal contamination in surface sediments from the Zhuyukou Waterway, Pingtan Island, Southeast China - Jianhua Liu; Xiuling Chen; Jie Liu; Binggui Cai; Yujie Guo (Regional Studies in Marine Science, 2025)

Blocking T-type calcium channels disrupts spermatogenesis in vivo and adversely affects spermatocytes in vitro by impairing mitochondrial function and autophagic flux - Xiuling Zhao; Lei Wang; Shiqin Huang; Lin Liu; Xiaorong Wang; Liping Pu; Hao Chen; Junyu Nie (Reproductive Toxicology, 2025)

All-in-one electrochromic windows based on hydrogels containing dual redox pairs for affordable and large-scale applications - Yuling Zhu; Qi Zhao; Chenglong Mu; Yahui Liu; Yuguo Xia; Xiuling Jiao; Dairong Chen; Ting Wang (Chemical Engineering Journal, 2025)

Ether-free PDMS-based composite electrolytes with intrinsic safety, high ionic conductivity and wide electrochemical window for solid state Li-metal batteries - Chenglong Mu; Jinyan Chen; Qi Zhao; Yahui Liu; Yuling Zhu; Zhang Dai; Xina Sui; Xiuling Jiao; Dairong Chen; Ting Wang (Chemical Engineering Journal, 2025)

Engineering resistance genes against tomato brown rugose fruit virus - Junzhu Wang; Tianxin Shen; Mengjie Song; Jiayi Fan; Yiqing Li; Toto Zen Chin; Yidan Yu; Fan Huang; Xiuling Yang; Changbao Li; Xueping Zhou; Chuanyou Li; et al. (Science China Life Sciences, 2025)

Woody Plant Encroachment Significantly Alters Grassland Soil Microbial Community: A Global Meta‐Analysis - Guoliang Sha; Shuyan Chen; Xuanchen Liu; Wanyu Xia; Hanwen Cui; Anning Zhang; Lizhe An; Zi Yang; Xia Zhao; Jing Zhang; Xiuling Yu; Jing Xiao; et al. (Global Ecology and Biogeography, 2025)
Aim Woody plant encroachment is reshaping grassland ecosystem functions worldwide. While its aboveground impacts are well documented, how this process alters microbial communities—key drivers of belowground processes—remains poorly understood. We aimed to (1) quantify the general effects of global woody plant encroachment on soil microbial community attributes in grasslands and (2) identify the abiotic and biotic factors driving these changes. Location Global grassland ecosystems. Time Period 2000–2024. Major Taxa Studied Soil microbial communities (bacteria, fungi). Methods We conducted a meta‐analysis of 241 paired observations to evaluate changes in microbial composition, diversity, biomass, activity and enzyme activity under woody plant encroachment. Results Woody plant encroachment significantly altered soil properties. Woody plant encroachment also promoted a comprehensive increase in microbial community diversity, biomass, microbial activity and enzyme activity, as well as changes in community composition. The nitrogen‐fixing status of the encroaching species (biotic factor) significantly affected microbial responses: encroachment by nitrogen‐fixing plants resulted in a higher abundance of Bacteroidetes, fungal richness, microbial biomass phosphorus and phosphatase activity compared to non‐nitrogen‐fixing plants. In addition, abiotic factors, such as mean annual temperature, soil organic carbon and total nitrogen were identified as key factors driving microbial responses. Specifically, mean annual precipitation, mean annual temperature and elevation jointly regulated the effects of woody plant encroachment on soil microbial community attributes by influencing plant and soil properties. Main Conclusions This meta‐analysis demonstrated that woody plant encroachment significantly reshaped soil microbial communities in grassland ecosystems. Our findings highlight the role of abiotic factors (climate, elevation, organic carbon and total nitrogen), and biotic factors (nitrogen‐fixing status) in mediating the response of soil microbial communities. These insights contribute to a better understanding of belowground ecological processes and provide valuable guidance for grassland management and predictions of biogeochemical cycles under global change.

Electronic structure modulating of PtFe dual-atom catalyst for efficient hydrogen splitting and almost 100 % selective hydrogenation of α,β-unsaturated aldehydes - Xinrui Liu; Yupeng Li; Dairong Chen; Xiuling Jiao; Yuguo Xia (Chemical Engineering Journal, 2025)

Identification of brevis radix (BRX) family genes in tomato (Solanum lycopersicum) and the function of SlBRX5 and SlBRX7 under cold stress - Xiuling Chen; Changhao Mao; Rui Lv; Hecheng Sun; Shusen Liu; Zhao Liu; Aoxue Wang (Plant Science, 2025)

Fabrication of Ti-MOF/Ti3C2 heterojunction with boosted activity for visible light-driven photocatalytic degradation - Xianghan Cheng; Zhongmin Liu; Ruilin Wang; Yajun Guo; Wenyuan Han; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Suijun Liu; Longlong Geng (Journal of Environmental Chemical Engineering, 2025)

Rapid cross-linking of MoS2 photothermal layers and their assembly of interface evaporators for desalination and environmental optimization - Zekun Zhang; Xiuling Li; Guangqi Liu; Shuo Qi; Jing Lv; Bo Ge; Tonghui Zhang; Guina Ren; Zhaozhu Zhang (Desalination, 2025)

Inhibition of recurrence and metastasis in triple-negative breast cancer through nanoparticle-mediated silencing of LPCAT1 to remodel ATP energy metabolism - Xiuling Li; Senlin Li; Haotian Li; Guo Wu; Huijie Zhao; Shaomin Liu; Xiaoding Xu; Phei Er Saw (Science China Life Sciences, 2025)

Functional molecule surface infiltration treatment for efficient all-inorganic perovskite light-emitting diodes - Shurui Chi; Yongjian Chen; Xiuling Li; Jiaqi Wang; Zixun Zhao; Zhuojian Li; Yanqin Miao; Xin Tong; Jinli Liu; Yuechuan Bi; Zongwen Liu; Zhiming Wang; et al. (Chemical Engineering Journal, 2025)

Silica Nanoparticles Induce SH-SY5Y Cells Death Via PARP and Caspase Signaling Pathways - Kai Ma; Tiantian Tian; Xinyue Li; Huan Pang; Xiaofan Ning; Meng Li; Jiali Li; Zhixuan Luo; Tianxiang Liu; Mengyue Liu; Mingqian Wang; Chao Zhao; et al. (Molecular Neurobiology, 2025)

The impact of Span80 single molecule and micelle forms on the structure and performance of polyamide nanofiltration membranes - Yue Miao; Xiaowen Huo; Yingying Zhao; Xiuling Liu; Haitao Wang; Jun Li; Na Chang (Journal of Water Process Engineering, 2025)

Application of composite biological control agent in postharvest preservation of cherry tomatoes - Fanyue Meng; Mozhen Cheng; Ziqi Zhou; Peiwen Wang; Shusen Liu; Zhao Liu; Zhengfeng Song; Xiuling Chen; Aoxue Wang (Physiological and Molecular Plant Pathology, 2025)

Comprehensive metabolome and transcriptome analyses shed light on the regulation of SlNF-YA3b in carotenoid biosynthesis in tomato fruit - Peiwen Wang; Siyu Ran; Yuanhang Xu; Fulei Mo; Fengshuo Li; Rui Lv; Fanyue Meng; Huixin Zhang; Yuxin Zou; Lei Yu; Tianyue Yu; Mozhen Cheng; et al. (Postharvest Biology and Technology, 2025)

Computational Modeling of the Prefrontal-Cingulate Cortex to Investigate the Role of Coupling Relationships for Balancing Emotion and Cognition - Jinzhao Wei; Licong Li; Jiayi Zhang; Erdong Shi; Jianli Yang; Xiuling Liu (Neuroscience Bulletin, 2025)

Long-term pollution status of microplastics in sediment of a typical mariculture area - Xiaodan Wang; Jianmin Zhao; Shuang Zhao; Xiuling Yan; Shuang Guo; Yongliang Liu; Qing Wang; Jianbai Zhang (Marine Pollution Bulletin, 2024)

A Machine Learning Approach for Behavioral Recognition of Stress Levels in Mice - Hao Song; Shirley Shimin Qiu; Binghao Zhao; Xiuling Liu; Yu-Ting Tseng; Liping Wang (Neuroscience Bulletin, 2024)

NaCl improves the vegetable quality of Mesembryanthemum crystallinum Linn. by increasing betacyanin and nutrient contents - Yanlu Liu; Qing Liu; Xiuling Liu; Yang Zhao; Yun Liu; Baoshan Wang; Min Chen (Plant and Soil, 2024)

Multi-scale modeling to investigate the effects of transcranial magnetic stimulation on morphologically-realistic neuron with depression - Licong Li; Shuaiyang Zhang; Hongbo Wang; Fukuan Zhang; Bin Dong; Jianli Yang; Xiuling Liu (Cognitive Neurodynamics, 2024)

Diversity and composition of active and total bacteria in rhizospheric soil in response to continuous cropping years of Panax notoginseng - Yuyan Liu; Limei Bao; Wanwan Sun; Yinshan Cui; Xiaoran Li; Xiuling Ji; Yunlin Wei; Yong Tan (Folia Microbiologica, 2024)

Diversity and functional traits of seed endophytes of Dysphania ambrosioides from heavy metal contaminated and non-contaminated areas - Weijun Gong; Qiaohong Li; Yungui Tu; Dian Yang; Yibin Lai; Wenting Tang; Wenqin Mao; Yue Feng; Li Liu; Xiuling Ji; Haiyan Li (World Journal of Microbiology and Biotechnology, 2024)

Pollution characteristics, potential source areas, and transport pathways of PM2.5 and O3 in an inland city of Shijiazhuang, China - Aifang Gao; Boyi Gao; Shaorong Li; Wenjie Yao; Wanting Sun; Xiuling Cao; Yuehua Liu; Hongliang Zhang; Baojun Zhang (Air Quality, Atmosphere & Health, 2024)

Diagnosis of pulmonary tuberculosis with 3D neural network based on multi-scale attention mechanism - Shidong Zhang; Cong He; Zhenzhen Wan; Ning Shi; Bing Wang; Xiuling Liu; Dailun Hou (Medical & Biological Engineering & Computing, 2024)

Fabrication and characterization of blue honeysuckle anthocyanins-loaded nanocomposite films and the application in pork preservation - Jiaxu Li; Xinhua Zhang; Jiale Lv; Jun Yang; Xiaochen Liu; Xiuling Zhang; Wentao Zhang (Food Hydrocolloids, 2024)

Sedimentary characteristics of ion-adsorption rare earth elements and assessment of their resource reuse potential due to soil and water erosion in western Fujian - Chen Xiaowei; Chen Xiuling; Chen Zhibiao; Cai Binggui; Chen Zhiqiang; Li Yue; Chen Feiyan; Wang Yi; Fan Yifei; Liu Jie (Environmental Monitoring and Assessment, 2024)

Inhibitory effect and action mechanism of perillaldehyde on the Fusarium graminearum in postharvest fresh ginger - Xiuling Meng; Weijie Wu; Ben Niu; Ruiling Liu; Huizhi Chen; Haiyan Gao; Hangjun Chen (Postharvest Biology and Technology, 2024)

Influence of freeze–thaw cycles on the compressibility of the clay of core-wall soil materials - Xiuling Ren; Enlong Liu; Qihao Yu; Zhenyu Zhang (Bulletin of Engineering Geology and the Environment, 2024)

GABA primes defense responses against Botrytis cinerea in tomato fruit by modulating ethylene and JA signaling pathways - Meiqi Li; Xinhua Zhang; Jiaoqi Li; Maratab Ali; Yuting Wang; Xiuling Liu; Fujun Li; Xiaoan Li (Postharvest Biology and Technology, 2024)

Influence spatial behavior of surface cracks and prospects for prevention methods in shallow loess tunnels in China - Junling Qiu; Dedi Liu; Kai Zhao; Jinxing Lai; Xiuling Wang; Zhichao Wang; Tong Liu (Tunnelling and Underground Space Technology, 2024)

Effects of extraction methods on the structure and functional properties of soluble dietary fiber from blue honeysuckle (Lonicera caerulea L.) berry - Run Ji; Xiuling Zhang; Chenghai Liu; Wentao Zhang; Xiaofeng Han; Hengtian Zhao (Food Chemistry, 2024)

Rht12b, a widely used ancient allele of TaGA2oxA13, reduces plant height and enhances yield potential in wheat - Yingjie Bian; Lingli Li; Xiuling Tian; Dengan Xu; Mengjing Sun; Faji Li; Lina Xie; Siyang Liu; Bingyan Liu; Xianchun Xia; Zhonghu He; Shuanghe Cao (Theoretical and Applied Genetics, 2023)

Combined use of Trichoderma harzianum and Clonostachys rosea to manage Botrytis cinerea infection in tomato plants - Fengshuo Li; Hossien Ghanizadeh; Wenwei Song; Shuang Miao; Hui Wang; Xiuling Chen; Jiayin Liu; Aoxue Wang (European Journal of Plant Pathology, 2023)

Nanoparticle (NP)-mediated APOC1 silencing to inhibit MAPK/ERK and NF-κB pathway and suppress breast cancer growth and metastasis - Shaomin Liu; Fengqian Zhang; Yixia Liang; Guo Wu; Rong Liu; Xiuling Li; Phei Er Saw; Zhonghan Yang (Science China Life Sciences, 2023)

VDAC1 Protein Regulation of Oxidative Damage and Mitochondrial Dysfunction-Mediated Cytotoxicity by Silica Nanoparticles in SH-SY5Y Cells - Xiaofan Ning; Xinyue Li; Kai Ma; Huan Pang; Tiantian Tian; Huifang Hao; Qiaohong Hou; Meng Li; Tianxiang Liu; Shanshan Hou; Haiying Du; Xiuling Song; et al. (Molecular Neurobiology, 2023)

Controls for phytolith accumulation in Moso bamboo leaves across China - Lijun Liu; Scott X. Chang; Chengpeng Huang; Xiuling Yu; Yuyou Zhi; Peikun Jiang (Science of The Total Environment, 2023)

3D Convolution neural network with multiscale spatial and temporal cues for motor imagery EEG classification - Xiuling Liu; Kaidong Wang; Fengshuang Liu; Wei Zhao; Jing Liu (Cognitive Neurodynamics, 2023)

Fine mapping and characterization of a major QTL for plant height on chromosome 5A in wheat - Lingli Li; Dengan Xu; Yingjie Bian; Bingyan Liu; Jianqi Zeng; Lina Xie; Siyang Liu; Xiuling Tian; Jindong Liu; Xianchun Xia; Zhonghu He; Yan Zhang; et al. (Theoretical and Applied Genetics, 2023)

Visual detection of Staphylococcus aureus based on immunomagnetic separation and polymerase spiral reaction - Yue Zhai; Haoyan Yu; Xingxing Liu; Mengfan Zhang; Rongpeng Han; Caihong Yin; Xingchi Liu; Hui Li; Juan Li; Xiuling Song (Food Control, 2023)

Microbiome - based agents can optimize composting of agricultural wastes by modifying microbial communities - Fengshuo Li; Hossein Ghanizadeh; Guangliang Cui; Jiayin Liu; Shuang Miao; Chang Liu; Wenwei Song; Xiuling Chen; Mozhen Cheng; Peiwen Wang; Yao Zhang; Aoxue Wang (Bioresource Technology, 2023)

Development and characterization of yeast-incorporated coating films for improving the postharvest shelf-life of snap beans - Xinmao Li; Hossein Ghanizadeh; Zhengyuan Han; Tiantian Li; Yinghui Li; Zhitao Dou; Youwen Qiu; Xiuling Chen; Yao Zhang; Jiayin Liu; Aoxue Wang (Postharvest Biology and Technology, 2023)

The Improving of Cd2+ Adsorption Performance of Hydrochar Obtained from Corn Straw Waste with KOH Activation - Yan Shi; Heng Li; Yushi Rong; Li Bai; Mingshu Chi; Xiuling Xu; Chenglin Li; Hao Bai; Yue Liu (Water, Air, & Soil Pollution, 2022)

Hybrid histidine kinase HisK2301 modulates carotenoid production to counteract cold-induced oxidative stress in Rhodosporidium kratochvilovae YM25235 under low temperature - Meixia He; Xiaoxia Yang; Tao Liu; Xiaoqing Zhang; Xiuling Ji; Yunlin Wei; Qi Zhang (Antonie van Leeuwenhoek, 2022)

A transgene-free method for rapid and efficient generation of precisely edited pigs without monoclonal selection - Kui Xu; Xiuling Zhang; Zhiguo Liu; Jinxue Ruan; Changjiang Xu; Jingjing Che; Ziyao Fan; Yulian Mu; Kui Li (Science China Life Sciences, 2022)

The impact of TOPBP1 mutations in human cancers on the DNA damage response - Zhenzhen Yan; Xiuling Ge; Jiaxu Wang; Feng Xu; Mengyao Li; Xiuhua Liu; Xiaochun Yu; Chen Wu (Genome Instability & Disease, 2022)

The Sm gene conferring resistance to gray leaf spot disease encodes an NBS-LRR (nucleotide-binding site-leucine-rich repeat) plant resistance protein in tomato - Huanhuan Yang; Hexuan Wang; Jingbin Jiang; Mingyue Liu; Zengbing Liu; Yinxiao Tan; Tingting Zhao; He Zhang; Xiuling Chen; Jingfu Li; Aoxue Wang; Minmin Du; et al. (Theoretical and Applied Genetics, 2022)

Construction of circRNA-related ceRNA networks in longissimus dorsi muscle of Queshan Black and Large White pigs - Kunlong Qi; Yingke Liu; Chenlei Li; Xinjian Li; Xiuling Li; Kejun Wang; Ruimin Qiao; Xuelei Han (Molecular Genetics and Genomics, 2022)

Molecular mapping and characterization of QBp.caas-3BL for black point resistance in wheat (Triticum aestivum L.) - Cuihe Liu; Jie Song; Siyang Liu; Jingdong Liu; Dengan Xu; Xiuling Tian; Yingjie Bian; Yachao Dong; Fengju Wang; Rongge Wang; Zhonghu He; Xianchun Xia; et al. (Theoretical and Applied Genetics, 2021)

Influence of Cr (VI) concentration on Cr (VI) reduction and electricity production in microbial fuel cell - Xiuling Zhang; Yuanfeng Liu; Congju Li (Environmental Science and Pollution Research, 2021)

The impact of policy mixes on new energy vehicle diffusion in China - Xiuling Liu; Fuji Xie; Haihua Wang; Chujiang Xue (Clean Technologies and Environmental Policy, 2021)

A cross-sectional survey based on blood VOCs, hematological parameters and urine indicators in a population in Jilin, Northeast China - Xiaocui Li; Yuanyuan Guo; Xiuling Song; Yinghua He; Huiwen Zhang; Hao Bao; Xinxin Li; Yushen Liu; Yue Zhai; Juan Wang; Kun Xu; Juan Li (Environmental Geochemistry and Health, 2019)

Adaptive growth response of exotic Elaeagnus angustifolia L. to indigenous saline soil and its beneficial effects on the soil system in the Yellow River Delta, China - Yan Qi; Junpeng Li; Chunxiao Chen; Lingxiao Li; Xiuling Zheng; Jing Liu; Tingting Zhu; Caihong Pang; Baoshan Wang; Min Chen (Trees, 2018)

Constructing a Guided Filter by Exploiting the Butterworth Filter for ECG Signal Enhancement - Ming Liu; HuaQing Hao; Peng Xiong; Feng Lin; ZengGuang Hou; Xiuling Liu (Journal of Medical and Biological Engineering, 2018)

The role of HMGB1 in BMSC transplantation for treating MODS in rats - Guanghui Xiu; Jie Sun; Xiuling Li; Hua Jin; Yichao Zhu; Xia Zhou; Ping Liu; Xinghua Pan; Jian Li; Bin Ling (Cell and Tissue Research, 2018)

Correction to: The catastrophic landside in Maoxian County, Sichuan, SW China, on June 24, 2017 - Junling Qiu; Xiuling Wang; Siyue He; Houquan Liu; Jinxing Lai; Lixin Wang (Natural Hazards, 2018)

Physiological and RNA-seq analyses provide insights into the response mechanism of the Cf-10-mediated resistance to Cladosporium fulvum infection in tomato - Guan Liu; Junfang Liu; Chunli Zhang; Xiaoqing You; Tingting Zhao; Jingbin Jiang; Xiuling Chen; He Zhang; Huanhuan Yang; Dongye Zhang; Chong Du; Jingfu Li; et al. (Plant Molecular Biology, 2018)

Native promoters of Corynebacterium glutamicum and its application in l-lysine production - Xiuling Shang; Xin Chai; Xuemei Lu; Yuan Li; Yun Zhang; Guoqiang Wang; Chen Zhang; Shuwen Liu; Yu Zhang; Jiyin Ma; Tingyi Wen (Biotechnology Letters, 2018)

The catastrophic landside in Maoxian County, Sichuan, SW China, on June 24, 2017 - Junling Qiu; Xiuling Wang; Siyue He; Houquan Liu; Jinxing Lai; Lixin Wang (Natural Hazards, 2017)

HBV X Protein induces overexpression of HERV-W env through NF-κB in HepG2 cells - Cong Liu; Lijuan Liu; Xiuling Wang; Youyi Liu; Miao Wang; Fan Zhu (Virus Genes, 2017)

Fine-mapping qFS07.1 controlling fiber strength in upland cotton (Gossypium hirsutum L.) - Xiaomei Fang; Xueying Liu; Xiaoqin Wang; Wenwen Wang; Dexin Liu; Jian Zhang; Dajun Liu; Zhonghua Teng; Zhaoyun Tan; Fang Liu; Fengjiao Zhang; Maochao Jiang; et al. (Theoretical and Applied Genetics, 2017)

Evaluation of growth and biochemical indicators of Salvinia natans exposed to zinc oxide nanoparticles and zinc accumulation in plants - Changwei Hu; Xu Liu; Xiuling Li; Yongjun Zhao (Environmental Science and Pollution Research, 2014)

Activation of elements in HERV-W family by caffeine and aspirin - Chunlan Liu; Yatang Chen; Shan Li; Honglian Yu; Jie Zeng; Xiuling Wang; Fan Zhu (Virus Genes, 2013)

MicroRNA-21 promotes the proliferation and inhibits apoptosis in Eca109 via activating ERK1/2/MAPK pathway - Fengxia Liu; Shutao Zheng; Tao Liu; Qing Liu; Meng Liang; Xiuling Li; Ilyar Sheyhidin; Xiaomei Lu; Wenya Liu (Molecular and Cellular Biochemistry, 2013)

Biochemical Responses of Duckweed (Spirodela polyrhiza) to Zinc Oxide Nanoparticles - Changwei Hu; Yimeng Liu; Xiuling Li; Mei Li (Archives of Environmental Contamination and Toxicology, 2013)

Compressibility and structural properties of jadeite, NaAlSi2O6 at high pressure - Xiuling Wu; Xiaoyu Fan; Fei Qin; Dawei Meng; Xiaoling Zhang; Long Chen; Weiping Liu; Jianping Zheng (Journal of Earth Science, 2013)

Metabolic engineering and flux analysis of Corynebacterium glutamicum for L-serine production - ShuJuan Lai; Yun Zhang; ShuWen Liu; Yong Liang; XiuLing Shang; Xin Chai; TingYi Wen (Science China Life Sciences, 2012)

A spatio-temporal data model for road network in data center based on incremental updating in vehicle navigation system - Huisheng Wu; Zhaoli Liu; Shuwen Zhang; Xiuling Zuo (Chinese Geographical Science, 2011)

Age, trace elements and Hf-isotope composition of zircon in eclogites from the sulu UHP belt, East-Central China: Neoproterozoic intrusion and subsequent Paleozoic and Early Mesozoic metamorphism - Jianping Zheng; Huayun Tang; Junhong Zhao; Yuping Su; Chunmei Yu; Qirong Wei; Qingsheng Liu; Xiuling Wu (Journal of Earth Science, 2010)

Bio-geomorphologic features and growth process of Tamarix nabkhas in Hotan River Basin, Xinjiang - Zhizhong Li; Shengli Wu; Shujiang Chen; Xiuling Chen; Jianhui Jin; Qi Liu (Journal of Geographical Sciences, 2010)

Complex microcolinearity among wheat, rice, and barley revealed by fine mapping of the genomic region harboring a major QTL for resistance to Fusarium head blight in wheat - Sixin Liu; Xiuling Zhang; Michael O. Pumphrey; Robert W. Stack; Bikram S. Gill; James A. Anderson (Functional & Integrative Genomics, 2006)

Stable Inheritance of the Antisense Waxy Gene in Transgenic Rice with Reduced Amylose Level and Improved Quality - Qiaoquan Liu; Zongyang Wang; Xiuhua Chen; Xiuling Cai; Shuzhu Tang; Hengxiu Yu; Jinliu Zhang; Menming Hong; Minghong Gu (Transgenic Research, 2003)

Microdissection of individual chromosomes of Thinopyrum intermedium and isolation of molecular markers that are useful in detecting Th. intermedium chromatin introgressed into wheat - Yuzhu Dong; Zhenlan Liu; Bao Liu; Bu Xiuling; Mengyuan He; Baiqu Huang; Shui Hao (Cereal Research Communications, 2002)

Advances of Hybrid Wheat Breeding in China - Aimin Zhang; Xiuling Nie; Dongcheng Liu; Xiaoli Guo (Cereal Research Communications, 2001)